The Utilization of Social Media by Presidential Candidates in The Formation of Political Image: A Study of Instagram Content During The 2024 Indonesian Presidential Election Campaign - Dhana Adhipratama (Jurnal Impresi Indonesia, 2025)
The 2024 Indonesian Presidential Election marked a significant shift in political communication strategies, with Instagram emerging as a key platform for image building and message dissemination. This study aims to analyze how the three presidential candidates—Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo—utilized Instagram during the critical campaign period (D-7 to D+7 of voting day) to construct political images and influence voter perception. Using a quantitative content analysis approach, 126 Instagram posts were examined based on variables such as content type, messaging themes, visual storytelling, and interactivity. The findings reveal that video content dominated (58.7%), with Anies being the most active user, emphasizing personal narratives and public engagement. Ganjar focused on national issues, while Prabowo highlighted symbolic leadership. Key themes included candidate character (60.3%), voter support (61.9%), and vote mobilization (48.4%). However, interactivity features like polls and live sessions were underutilized. The study highlights the strategic role of digital storytelling and platform affordances in shaping political personas, supporting theories of framing and self-presentation. It suggests that successful political campaigns require not only compelling content but also platform literacy and two-way engagement strategies. The research contributes to the evolving discourse on digital democracy and offers practical insights for political actors navigating social media ecosystems.